Biology and Management of Florida Betony (Stachys floridana) in Ornamental Plants in Landscape Planting Beds - Thomas Smith; Chris Marble (EDIS)
Florida betony (Stachys floridana) is a perennial weed in Florida landscape planting beds, gardens, turfgrass, and agricultural production systems. This new 4-page article is written for green industry professionals and others to aid in the identification and management of Florida betony in and around ornamental plants in landscape planting beds. Written by Thomas Smith and Chris Marble, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep597